Specific of constitutional-legal legislation, accepted in a period from 1995 to 2007 (Journal of actual problems of jurisprudence, 2018)
This article is devoted to the third fourth stageof formation anddevelopment of the constitutionallegislative of the Kazakhstan, whichincludes the period-1995-2007 years. Accordingly, in thearticle considers thecontent ofthe constitutional and legalacts adopted inthis period, and also consider their analyzes. In conclusionabout the meaning androle of the constitutionallegislativeof the Kazakhstanadopted inthis period, whichbecame the basisfor theformation and development of the constitutionallegislativeof the sovereignand independent of Republic of the KazakhstanKey words: constitution, constitutional legislation, public domain, private domain, political reform, state mechanism, local self-government.